Gestión de talento humano de la microempresa tecni servicio JF Vizuete en la ciudad de Babahoyo. - Diaz Salas, Jhon Jairon (2022)
Currently, the world in which we live is competitive, which requires collaborators committed to the entity to achieve the desired results, so the productivity of both the employee and the microenterprise grows, therefore, the main problem was an analysis of the current state of the human talent management system in the microenterprise, allowing to determine the processes of Integrating, Organizing, Rewarding, Developing, Retaining and Auditing people, therefore, the general objective of this present study is to diagnose the talent management of the microenterprise. Tecni Servicio Jf Vizuete microenterprise of the city of Babahoyo through the model of the talent management system, due to which information must be compiled for it based on theory. which information was obtained through a questionnaire to obtain quantitative data and an interview was also conducted to obtain comments. It has been determined that the performance of the employees has shortcomings, due to this they do not develop personal skills that allow them to function in the workplace, therefore, there is an inadequate administration allowing that the work carried out by the staff sometimes accumulates the which does not favor them, causing physical and mental fatigue when executing their work tasks.